Application of molecular biological tools for monitoring efficiency of trichloroethylene remediation. (October 2019) - Wu, Yi-Ju; Liu, Pao-Wen Grace; Hsu, You-Siang; Whang, Liang-Ming; Lin, Tsair-Fuh; Hung, Wei-Nung; Cho, Kun-Ching
Abstract: Trichloroethylene (TCE) is one of the most ubiquitous halogenated organic compounds of concerns of carcinogens in groundwater in Taiwan. Bioremediation has been recognized as a cost-effective approach in reducing TCE concentration. Five pilot-scale wells were constructed to monitor TCE concentrations in contaminated groundwater. With injection of EOS®, TCE was effectively degraded to 42%–93% by the end of 175 days. The biostimulation with EOS® was useful in establishing a micro-site anaerobic but with limited contribution. Dilution of the aquifer movement also caused the TCE reduction among injection and monitoring wells. The degradability was affected by the location and the proximity from the injection well. TCE concentrations found to be negatively correlated with the associated Dehalococcoides spp. and functional genes levels. Dhc concentration of 10 8 copies L −1 caused the initial 40% of TCE degradation. The well with the optimal degradation owned tceA of 10 9  cells L −1 . T-RFLP results indicate the wells with the superior TCE degradability also performed the highest Shannon index number (means the highest diversity), which occurred on the same day that Dhc levels started to enlarge. Desulfovibrio desulfuricans and Desulfuromonas chloroethenica were predominant species identified in the T-RFLP fingerprint profile. In brief, a variety of different factors including well locations, geochemical indicators, and microbial contribution were useful to explain the site-specific optimal TCE remediation approach. The consistence among TCE degradation, Dhc growing pattern, functional gene levels, and the dynamics of the microbial community structure present the novelty of this study. Highlights: TCE degradation achieved approximately 40% when Dehalococcoides sp. levels achieved 10 8 copies L −1 . T-RFLP results indicate the superior TCE degradability correlated with the highest diversity estimated by H index. Desulfovibrio desulfuricans and Desulfuromonas chloroethenica were predominant species in the T-RFLP profile. The TCE degradation of 42%-93% was due to EOS® injection in a micro-site anaerobic condition and dilution of the aquifer.